1995
DOI: 10.1111/j.1468-036x.1995.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasoned equity offerings and the short‐ and long‐run performance of initial public offerings in the UK

Abstract: In contrast to the US practice, rights issues is the predominant method of raising additional equity capital in the London market. the UK evidence for the period 1980-1991 provides no support to the hypothesis that IPO firms deliberately underprice to signal their quality and facilitate subsequent seasoned equity offerings. the level of initial returns is related neither to the size of the issue nor to the price response at the announcement of a rights issue. the results demonstrate, however, that firms with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
2
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 27 publications
(28 reference statements)
9
50
2
4
Order By: Relevance
“…A stock price decline has been observed by Hansen (1989) and Eckbo and Masulis (1992) in US. In United Kingdom 2-day excess return of -1.3% (Levis, 1995) and -1.88% (Slovin et al, 2000) has been observed. A negative excess stock returns has also been observed in France (Gajewski and Ginglinger, 1998), New Zealand (Marsden, 2000), Netherlands (Kabir and Roosenboom, 2003) and Hong Kong (Ching et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A stock price decline has been observed by Hansen (1989) and Eckbo and Masulis (1992) in US. In United Kingdom 2-day excess return of -1.3% (Levis, 1995) and -1.88% (Slovin et al, 2000) has been observed. A negative excess stock returns has also been observed in France (Gajewski and Ginglinger, 1998), New Zealand (Marsden, 2000), Netherlands (Kabir and Roosenboom, 2003) and Hong Kong (Ching et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Loughran and Ritter (1995) find postissue underperformance of almost 10% per year, over a five-year period, between SEO issuers and similar non-issuing firms in the U.S. Additional evidence of underperformance is reported in Spiess and Affleck-Graves (1995), Jegadeesh (2000) and Loughran and Ritter (2000). Using Japanese and U.K. market data, Cai and Loughran (1998), Kang, Kim, and Stulz (1999), Levis (1995), and Suzuki (2000) also find underperformance following SEOs. However other authors like Brav, Geczy, and Gompers (2000), Mitchell and Stafford (2000), and Eckbo, Masulis, and Norli (2001) find little or no evidence of underperformance.…”
Section: Introductionmentioning
confidence: 88%
“…For placing firms, the equal-weighted and value-weighted BHARs are À 3.29% and À 7.15%, respectively. Similar to the U.S. studies, Ho (2005) also finds that the calendar-time abnormal returns are smaller and Spiess and Affleck-Graves (1995) 1975-19891247 À6.10 a,# NA Loughran and Ritter (1995) 1970-1990 3702 À9.10 a,# NA Loughran and Ritter (2000) 1973-1996 6461 À5.64 b *** À 3.84 b *** Brav et al (2000) 1975-1992 3775 À3.90 a,# À 3.40 a,# À4.44 b *** À 1.68 b À2.28 c À 2.28 c ** Eckbo et al (2000) 1964-1995 3315 À4.80 a *** À 2.20 a À1.44 b À2.04 b Jegadeesh (2000) 1970-1993 2992 À4.90 a ** NA À5.40 b *** NA À3.72 c *** NA Mitchell and Stafford (2000) 1961-1993 4439 À2.70 a *** À 1.10 a À3.96 b *** À 0.36 b Panel B Japanese data Cai and Loughran (1998) 1971-19921389 À3.50 a ** NA Kang et al (1999) 1980-1988 888 À9.80 a *** NA Panel C U.K. data Levis (1995Levis ( ) 1980Levis ( -1988 À15.10 d *** NA Suzuki (2000) 1991-1996 689 À11.50 a *** NA This table provides brief details of selected prior papers that study the long-horizon performance of firms after issuing SEOs. It provides details about the sample period of the study and the type of weighting scheme used to construct portfolios.…”
Section: Review Of Previous Researchmentioning
confidence: 98%
See 2 more Smart Citations